2013
DOI: 10.1292/jvms.12-0161
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in VKORC1 and Its Effect on Enzymatic Activity in Japanese Warfarin-Resistant Rats

Abstract: ABSTRACT. Warfarin is a rodenticide commonly used worldwide. It inhibits coagulation of blood by inhibiting vitamin K 2,3-epoxide reductase (VKOR) activity. An inadequate supply of vitamin K blocks the production of prothrombin and causes hemorrhage. Recently, warfarin-resistant brown rats (Rattus norvegicus) were found around the Aomori area of Japan. There is no significant difference in the metabolic activity of warfarin in sensitive and resistant brown rats. To clarify the mechanism underlying warfarin res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Based on the structure of the cyanobacterial enzyme, it was suggested that warfarin binds at the same site at the quinone seen in the structure (and that vitamin K epoxide would also interact at this site) [47]. This is consistent with the locations of some of the mutations which alter the sequence of rat VKOR conferring resistance to warfarin and those which are associated with hereditary clotting deficiencies in humans [55,[62][63][64][65][66][67]. Many of these variant forms of VKOR have lower catalytic activity than the wild-type and it is presumed that this loss of fitness is a "price worth paying" for resistance to rat poison [68].…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Based on the structure of the cyanobacterial enzyme, it was suggested that warfarin binds at the same site at the quinone seen in the structure (and that vitamin K epoxide would also interact at this site) [47]. This is consistent with the locations of some of the mutations which alter the sequence of rat VKOR conferring resistance to warfarin and those which are associated with hereditary clotting deficiencies in humans [55,[62][63][64][65][66][67]. Many of these variant forms of VKOR have lower catalytic activity than the wild-type and it is presumed that this loss of fitness is a "price worth paying" for resistance to rat poison [68].…”
mentioning
confidence: 65%
“…Using a homology model based on the cyanobacterial structure, docking with AutoDock Vina as implemented in Chimera [69,70], predicted that both dicoumarol and warfarin would bind at the base of the cleft with partially overlapping binding sites ( Figure 3). These models predict that the ligands bind close to some residues implicated in warfarin resistance, notably Ala-26, Trp-59, Glu-67, His-68, Gly-71, Leu-120 and Tyr-139 [55,[62][63][64][65][66][67]71].…”
mentioning
confidence: 99%
“…28,41 Studies on the genetic basis of warfarin resistance led to the development and usage of molecular methods for identifying and screening rodents, which are more convenient and economical than the LFP and BCR methods currently used in China. 2,9,14,15,[24][25][26] Studies of the molecular resistance mechanism in rats could facilitate the development of molecular tools for rapid screening of rats for anticoagulant resistance.…”
Section: Discussionmentioning
confidence: 99%
“…18 In Norway rats, at least 10 Vkorc1 mutations were suggested to be associated with anticoagulant resistance based on in vivo, in vitro and in silico studies. 9,14,15,[19][20][21][22][23][24][25][26] Some Vkorc1 mutations, for example Tyr139Cys/Phe/Ser, have been widely used as genetic markers for screening or monitoring resistant commensal rodent species in Europe. 2,14 However, those genetic markers may not be applicable to rodents in other regions as other resistance Vkorc1 mutations may be present in different local populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation